Comparing the Concept of Halal Tourism in Indonesia, Thailand, and Malaysia - Imam Mawardi (MOZAIK HUMANIORA, 2021)
This study aimed to illustrate the development and thoughts of halal tourism in several Southeast Asian countries. The study was conducted using library research to examine previous references, such as books, media journals, and websites. Results show that the globalization of the tourism industry has developed due to the rising demand from Muslim tourists which led to the birth of halal tourism. This condition is most prominent in the countries with large Muslim population. However, tourism is much in demand and practised in both Muslim majority and Muslim minority countries. Halal tourism trends provide many benefits for economic growth through consumers who are mostly Muslim. In Indonesia, Ulama Council as a supporter of halal tourism has no formal legality or legal certainty, unlike JAKIM in Malaysia. Nevertheless, the concept of halal tourism itself is still different in each country. In conclusion, the concept of halal tourism do not merely emphasise religious values, but also on the economic sector.